Acupuncture: A Promising Approach for Comorbid Depression and Insomnia in Perimenopause - Zhao FY (Dove Medical Press, 2021)
Fei-Yi Zhao,1– 3 Qiang-Qiang Fu,4 Sarah J Spencer,1,5 Gerard A Kennedy,1,6,7 Russell Conduit,1 Wen-Jing Zhang,2 Zhen Zheng1 1School of Health and Biomedical Sciences, RMIT University, Bundoora, Victoria, 3083, Australia; 2Shanghai Municipal Hospital of Traditional Chinese Medicine, Shanghai University of Traditional Chinese Medicine, Shanghai, 200071, People’s Republic of China; 3Department of Nursing, School of International Medical Technology, Shanghai Sanda University, Shanghai, 201209, People’s Republic of China; 4Yangpu Hospital, School of Medicine, Tongji University, Shanghai, 200090, People’s Republic of China; 5ARC Centre of Excellence for Nanoscale Biophotonics, RMIT University, Bundoora, Victoria, 3083, Australia; 6School of Science, Psychology and Sport, Federation University, Mount Helen, Victoria, Australia; 7Institute for Breathing and Sleep, Austin Health, Heidelberg, Victoria, 3084, AustraliaCorrespondence: Wen-Jing ZhangDepartment of Psychiatry, Shanghai Municipal Hospital of Traditional Chinese Medicine, Shanghai University of Traditional Chinese Medicine, Shanghai, 200071, People’s Republic of ChinaTel +86 021-6605 0366Email 1072@szy.sh.cn.comZhen ZhengSchool of Health and Biomedical Sciences, College of Science, Engineering and Health, RMIT University, P.O. Box 71, Bundoora, Victoria, 3083, AustraliaTel +61 9925 7167Fax +61 3 9925 7178Email zhen.zheng@rmit.edu.auAbstract: Comorbid depression and insomnia are ubiquitous mental complaints among women going through the perimenopausal stage of life and can result in major decline in quality of life. Antidepressive agents combined with/without hypnotics, and/or hormone therapy are currently the most common treatment for perimenopausal depression (PMD) and insomnia (PMI). Balancing the benefits of these pharmacotherapies against the risk of adverse events (AEs) is a difficult task for both clinicians and women. There has been a growing body of research regarding the utilization of acupuncture for treatment of PMD or PMI, whereas no studies of acupuncture for comorbid PMD and PMI have appeared. In this review, we summarize the clinical and preclinical evidence of acupuncture as a treatment for PMD or PMI, and then discuss the potential mechanisms involved and the role of acupuncture in helping women during this transition. Most clinical trials indicate that acupuncture ameliorates not only PMD/PMI but also climacteric symptoms with minimal AEs. It also regulates serum hormone levels. The reliability of trials is however limited due to methodological flaws in most studies. Rodent studies suggest that acupuncture prolongs total sleep time and reduces depression-like behavior in PMI and PMD models, respectively. These effects are possibly mediated through multiple mechanisms of action, including modulating sex hormones, neurotransmitters, hypothalamic-pituitary-adrenal axis/hypothalamic-pituitary-ovary axis, oxidative stress, signaling pathways, and other cellular events. In conclusion, acupuncture is a promising therapeutic strategy for comorbid depression and insomnia during perimenopause. Neuroendocrine modulation is likely to play a major role in mediating those effects. High-quality trials are required to further validate acupuncture’s effectiveness.Keywords: acupuncture, perimenopause, insomnia, depression, comorbid, mechanisms